Assessment of Knowledge and Practice of 3D printing amongst the dentists of Lahore - Nauman Ahmed Noor, Aneela Qaisar, Abdul Rehman Shahid, Maheen Goryyah, Haider Haye, Alishba Imran, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The development of digital technologies in dentistry resulted in the introduction of 3 D printing. The faster manufacturing rate and patient-friendly approach of this technology have revolutionized dentistry. Aim: The aim of this study was the assessment of knowledge and practices of 3 D printing technology in Lahore. Methods: The cross-sectional study was conducted in private teaching institutes and private clinics of Lahore. A well structuedquestionnaie consisting of 20 questions was randomly distributed in 141 particapants. Data was eanalysed by SPSS vesion 23. The results were presented in percentages. Results: The majority 108(78%) of the participants did not use 3D printing technology during the past five years,, and the 86(61%) used it once a year, during their clinical practice. Most of the respondents 81(57.4%) were aware of Stereolithographic technique of 3 D printing. Temporary crowns 30(21.3%) were fabricated by 3 D printing. PMMA 63(44.7%) and PEEK 54(38.3%) were the most commonly used polymers, while Zirconia126(89.4%) and Titanium alloys117(83%) were mostly used for the fabrication of 3D printed dental prosthesis. Conclusion: Majority of the particiapants were not aware of 3 D printing technique and materials used for the fabrication of 3 D printes appliances. Most participants did not use 3D printing in their clinical practices. There was no current information about 3D printing technology and techniques in the undergraduate syllabus and courses of teaching. Practical implications: The future of dentistry involves using newer technology and keeping abreast with upcoming techniques for delivering better and more efficient healthcare. Most of these technologies are already available in market, but putting them to good use and familiarizing with them is the need of hour fo Pakistani dentist. Keywords: 3D printing, dental prosthesis, rapid protoyping, polymethyl meth acrylate (PMMA), Stereolithography Apparatus